2015
DOI: 10.1007/s12274-015-0739-5
|View full text |Cite
|
Sign up to set email alerts
|

Extreme biomimetic approach for developing novel chitin-GeO2 nanocomposites with photoluminescent properties

Abstract: This work presents an extreme biomimetics route for the creation of nanostructured biocomposites utilizing a chitinous template of poriferan origin. The specific thermal stability of the nanostructured chitinous template allowed for the formation under hydrothermal conditions of a novel germanium oxide− chitin composite with a defined nanoscale structure. Using a variety of analytical techniques (FTIR, Raman, energy dispersive X-ray (EDX), near-edge X-ray absorption fine structure (NEXAFS), and photoluminescen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
48
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 65 publications
(53 citation statements)
references
References 68 publications
(97 reference statements)
1
48
0
Order By: Relevance
“…The experimental data for a-SiO2 is from Mozzi and Warren which agrees well with our simulated data for the averaged Si-O-Si bridging angle which may be a little lower than from later measurements. The simulated a-GeO 2 model has a density is 3.351 g/cm 3 which is close to the experimental value of 3.69 ± 0.02 g/cm 3 [23]. The calculated pair distribution function (PDF) g(r) for this model is shown in Fig.…”
Section: Resultssupporting
confidence: 78%
See 1 more Smart Citation
“…The experimental data for a-SiO2 is from Mozzi and Warren which agrees well with our simulated data for the averaged Si-O-Si bridging angle which may be a little lower than from later measurements. The simulated a-GeO 2 model has a density is 3.351 g/cm 3 which is close to the experimental value of 3.69 ± 0.02 g/cm 3 [23]. The calculated pair distribution function (PDF) g(r) for this model is shown in Fig.…”
Section: Resultssupporting
confidence: 78%
“…A more recent account is given by Dianov and Mashinsky [2] and the references cited therein. Recently, its utilization as a photoluminescent biomimetic composite glass has been demonstrated [3]. Germania glass exhibits a lower glass transition temperature T g (~790 K) than SiO 2 based glasses [4].…”
Section: Introductionmentioning
confidence: 99%
“…In some of the earlier studies chitin isolated from different organisms showed nanofibrous and porous surface morphologies (Zhang et al., ; Yen and Mau, ,b). Some other reports revealed only nanofibrous surface structure for chitin isolates from different organisms (Ifuku et al., ; Ifuku et al., ; Wysokowski et al., ; Mushi et al., ). Recently several studies on chitin surface morphology reported the porous and fibrous surface organization (Paulino et al., ; Yen et al., ; Wysokowski et al., ).…”
Section: Discussionmentioning
confidence: 93%
“…The pellets for electrochemical measurements consisted of 85% of the a- The mass of the electrodes was in the range of 7 to 9 mg and a geometric surface area of one electrode was 0.8 cm 2 . As an electrolyte for electrochemical measurements 6 mol l À1 KOH was used.…”
Section: Electrochemical Measurementsmentioning
confidence: 99%